2020
DOI: 10.21276/ssr-iijls.2020.6.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and Control of Covid-19 (Corona Virus Disease 2019) By Non-invasive (h.i.p) Non-drug Therapy in Combination Anti-influenza an (Oseltamivir (rx) Tamiflue) Drug-Novel Case Report

Abstract: Background:Covid-19 is a new born sibling of the influenza family of SARS-CoV-2, named on February 11, as a new type of corona virus by the WHO. Covid-19 indicates its close relationship with activity and approaches with the SARS virus, which further triggered as epidemic in 2003 and 2004 and now similar lung triggered by SARS-CoV-2 is called Covid-19 (Corona Virus Disease 2019). Methods: A combination of integrative therapies were administered to a 27 year old female positive with unknown SARS-CoV identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Recently, scientists have reported anti-viral activity of Azadirachta indica against coronaviruses as a result of the urgency required for the development of a specific anti-viral drug for the prevention, treatment, and management of COVID-19. Pooladanda et al [75]; Borkotoky and Banerjee [76]; Ather and Costigliola [77] reported possible beneficial effect of Azadirachta indica in the treatment of SARS-CoV-2 infections.…”
Section: Abrus Precatorius Linn Gaertnmentioning
confidence: 99%
“…Recently, scientists have reported anti-viral activity of Azadirachta indica against coronaviruses as a result of the urgency required for the development of a specific anti-viral drug for the prevention, treatment, and management of COVID-19. Pooladanda et al [75]; Borkotoky and Banerjee [76]; Ather and Costigliola [77] reported possible beneficial effect of Azadirachta indica in the treatment of SARS-CoV-2 infections.…”
Section: Abrus Precatorius Linn Gaertnmentioning
confidence: 99%
“…A recent molecular docking study reported that some flavonoids and anthraquinones in M. oleifera may inhibit some proteins in SARS-CoV2, thus preventing its replication ( Hamza et al, 2020 ). In a study of COVID-19 patients, capsules of M. oleifera leaf extracts and other plants demonstrated promising therapeutic results that require further investigations ( Ather and Costigliola, 2020 ). Hypokalemia (potassium deficiency) has been reported in COVID-19 patients, resulting from an irregularity or disorder of the renin-angiotensin system due to decreased ACE2 activity.…”
Section: Combating Viruses With Natural Therapiesmentioning
confidence: 99%
“…[22] Asymptomatic infectivity has also been reported hence suggesting selfisolation. [23] Temporary recommendations under International Health Regulations were laid down to contain the accelerating pace of COVID-19 with paucity of treatment options [24] some of the crucial being by practicing self-hygiene and social distancing in addition to early detection and isolation. [25,26]…”
Section: Graphical Abstractmentioning
confidence: 99%